1983
DOI: 10.1111/j.2044-835x.1983.tb00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Does repetition of the question influence children's performance in conservation tasks?

Abstract: Three experiments are reported which evaluate Rose & Blank's claim that repetition of the conservation question in the traditional conservation task is interpreted by the child as a cue to change his judgement. Experiment 1 indicated that repetition of the conservation question per se does not lead to a change of judgement in the child. Experiment 2 demonstrated that the facilitatory influence of Rose & Blank's one‐judgement procedure was specific to number conservation tasks. This procedure was found not to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…They were explained either by attention shift determined by differences between the two successive displays (Levin, Gilat, & Zelniker, 1980) or by adherence to conversational rules according to which a question repeated twice deserves different answers (Neilson, Dockrell, & McKechnie, 1983;Rose & Blank, 1974;Samuel & Bryant, 1984;Siegal, Waters, & Dinwiddy, 1988). Such phenomena were previously observed among young children, mostly those in preschool.…”
Section: Discussionmentioning
confidence: 93%
“…They were explained either by attention shift determined by differences between the two successive displays (Levin, Gilat, & Zelniker, 1980) or by adherence to conversational rules according to which a question repeated twice deserves different answers (Neilson, Dockrell, & McKechnie, 1983;Rose & Blank, 1974;Samuel & Bryant, 1984;Siegal, Waters, & Dinwiddy, 1988). Such phenomena were previously observed among young children, mostly those in preschool.…”
Section: Discussionmentioning
confidence: 93%
“…However, it is noteworthy that preschoolers do not alter their quantity judgments if, in between making those judgments, they are not presented with the visible transformation of the array that is standard in Piagetian conservation experiments (Halford & Boyle, 1985). Thus, repetition of a quantity question does not in itself lead young children to alter their judgment (Neilson, Dockrell, & McKechnie, 1983). Still, repeated questioning cannot be entirely ruled out as a factor in the current design because in between the two questions children received the advice, and this might have had an analogous effect to visible transformations in conservation tasks.…”
Section: Discussionmentioning
confidence: 99%
“…On notransformation trials, a second judgment is requested after an interval without any transformation being performed. Neilson, Dockrell, and McKechnie (1983) have shown that repetition of the question per se does not influence children to change their judgments. If 3-4-year-olds have a tendency to give inconsistent judgments for any reason other than failure to interpret the transformation, they should show a similar level of consistency under both conditions.…”
Section: Discussionmentioning
confidence: 99%